Health and safety in emergency management and response - Stahl, Dana L., 1965- (John Wiley & Sons, Inc., 2021)
"This book familiarizes personnel serving as Emergency Managers, Safety Officers, Assistant Safety Officers, and in other safety-relevant Incident Command System (ICS) roles with physical and psychosocial hazards and stressors that may impact the health and safety of workers and responders in an All-Hazards Response, and ways to minimize exposure. This book provides knowledge on regulations and worker safety practices to the Safety Officer with an emergency responder background, and provides the tools for the Safety Officer with an industrial hygiene or safety professional background that help them be successful in this role. In order to work together effectively, it is important that anyone responding to an emergency be familiar with all standards and protocols. Topics include: Overview of Safety in Emergencies, OSHA's Role in Emergency Response, Emergencies and Related Hazards, Safety and Regulatory Requirements, Safety Training During a Response, Industrial Hygiene and Medical Monitoring Requirements, Psychological Hazards in an Emergency Response and Behavioral Health Management, The Role of the Safety Officer, The Role of the Technical Specialist, Incorporating Safety in Emergency Planning, Safety in Drills and Exercises, Safety in Continuity of Operations"- Resumé vydavatel
Keywords: havarijní plánování; zdraví a hygiena; krizový management; disaster planning; health and hygiene; crisis management; elektronické knihy; monografie; electronic books; monographs